2008
DOI: 10.3113/fai.2008.0213
|View full text |Cite
|
Sign up to set email alerts
|

A Simpler Device for Measuring the Mobility of the First Ray of the Foot

Abstract: This study demonstrated that the EMC device is both reliable and valid for measuring the mobility of the first ray of the foot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Based on clinical experience, Root et al proposed that the normal movement of the first ray was 5 mm of dorsiflexion and 5 mm of plantarflexion in the sagittal plane [ 22 ], but they did not directly measure FRM with any scientific means. Later, various studies have been carried out using different measurement instruments to try to quantify FRM [ 9 , 10 , 32 ]. However, none of those instruments takes into account the first ray movement in the frontal plane.…”
Section: Discussionmentioning
confidence: 99%
“…Based on clinical experience, Root et al proposed that the normal movement of the first ray was 5 mm of dorsiflexion and 5 mm of plantarflexion in the sagittal plane [ 22 ], but they did not directly measure FRM with any scientific means. Later, various studies have been carried out using different measurement instruments to try to quantify FRM [ 9 , 10 , 32 ]. However, none of those instruments takes into account the first ray movement in the frontal plane.…”
Section: Discussionmentioning
confidence: 99%
“…Klaue et al introduced a device that measures dorsal first metatarsal displacement with a numeric value [9]. The validity and reliability of the ''Klaue Device'' has been demonstrated in many studies and has been compared with others methods or radiological investigations [10][11][12][13][14][15][16][17]. Several authors quantify a pathological dorsal hypermobility as a displacement, regardless of the test used, of more than 10 mm [3,9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…More simple instruments have been subsequently created aiming at solving some of the aforementioned inconveniences [18,19]. However, some studies have reported only limited concordance and data reliability [16,20].…”
Section: Introductionmentioning
confidence: 99%